Evaluasi Sarana dan Prasarana Kawasan Minapolitan Berbasis QSPM - Tenri Sannawati; Mimi Arifin; Sri Aliah Ekawati (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2018)
Pangkep Regency, especially the Maccini Baji Hamlet, is one of the areas that has the potential to be developed as a minapolitan area. Therefore, in its development it is necessary to increase the facilities and infrastructure supporting the Minapolitan area. The purpose of this study was to analyze the feasibility of the infrastructure URL in Dusun Maccini Baji and formulate a strategy to improve the infrastructure. Data collection methods used are, observation, interviews, and literature studies. The analytical methods used are qualitative descriptive analysis, quantitative analysis, SWOT analysis, Internal Factor Evaluation (IFE) Analysis, External Factor Evaluation (EFE) Analysis, and Quantitative Strategy Planning Matrix (QSPM) Analysis. The results of this study indicate that the IFE value is 1.97 (positive) and EFE 1.3 (positive). The coordinate point in the Kuandran I contest is growth. Based on the QSPM table, the alternative strategy has a typical TAS. The first alternative is TAS 10.28, while the second alternative is TAS 10.53. Based on the total results of each alternative, the most appropriate alternative strategy to be implemented in the Minapolitan area is the Fast Growth Strategy.